Washington 101 - Green, M. author. aut Link
XI, 270 p. 15 illus.
Keywords: Washington 101 offers a layman's introduction to the richness and diversity of the nation's capital. An exploration of the history, politics, architecture, and people of the city and region, Washington 101 is a must-read for anyone curious to learn more about Washington.